2015
DOI: 10.2147/copd.s89814
|View full text |Cite
|
Sign up to set email alerts
|

Balance impairment and systemic inflammation in chronic obstructive pulmonary disease

Abstract: Background/purposeChronic obstructive pulmonary disease (COPD), especially in severe forms, is commonly associated with systemic inflammation and balance impairment. The aim of our study was to evaluate the impact on equilibrium of stable and exacerbation (acute exacerbation of COPD [AECOPD]) phases of COPD and to investigate if there is a connection between lower extremity muscle weakness and systemic inflammation.MethodsWe enrolled 41 patients with COPD (22 stable and 19 in AECOPD) and 20 healthy subjects (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 19 publications
2
42
0
2
Order By: Relevance
“…Age and other features may include lower limb muscle weakness, overall fatigue, dizziness, diferent functional impairment, body imbalance and others [14].…”
Section: Balance Disorders: Nosology Prevalence Clinical Consequencesmentioning
confidence: 99%
“…Age and other features may include lower limb muscle weakness, overall fatigue, dizziness, diferent functional impairment, body imbalance and others [14].…”
Section: Balance Disorders: Nosology Prevalence Clinical Consequencesmentioning
confidence: 99%
“…In support of this hypothesis, recent reports have shown that COPD in advanced stages is associated with an increased history of falls, balance impairment, and lower extremity muscle weakness. [65][66][67][68] Our results highlight that intercostal and intrinsic foot muscle Ca 21 signaling dysregulation occurs in cigarette smoke exposure. Understanding in more detail the pathophysiology of COPD and its effects in different skeletal muscles could help to further our knowledge of the natural history of the disease and to develop targeted treatments aimed to improve the performance of specific muscle groups.…”
Section: Limitations Of the Mouse Model Of Cigarette Smokementioning
confidence: 62%
“…We hypothesize that intrinsic foot muscle dysfunction could contribute to the increased susceptibility to falls in individuals with chronic COPD. In support of this hypothesis, recent reports have shown that COPD in advanced stages is associated with an increased history of falls, balance impairment, and lower extremity muscle weakness …”
Section: Discussionmentioning
confidence: 75%
“…Regarding postural steadiness, the study conducted by Tudorache et al 37 showed that the presence of COPD with stable or exacerbation phases is associated with impairment in postural steadiness. Our results showed that hospitalization led to impairment in postural steadiness.…”
Section: Discussionmentioning
confidence: 99%